ANALISIS PENERAPAN MODEL PEMBELAJARAN CONNECTED UNTUK MENGEMBANGKAN KETERAMPILAN BERKOMUNIKASI SISWA SEKOLAH DASAR - Dessy Mega Harumawati; Suryanti; Neni Mariana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Communication skill is one of the fundamental skill which needed in everyday life, both in academic and social contexts. Communication skill cover a variety of aspects, including the ability to convey ideas clearly, listen well, interact with others effectively, and use language appropriately. This skill is also found in the skill of being persuasive to other people. However, based on observations in the field, it was found that the majority of 6thGrade Students at UPT SD Negeri 192 Gresik did not understand the correct use of persuasive sentences. From these problems, an appropriate technique, method, strategy or learning model is needed to develop persuasive communication skill in students. A connected type of integrated learning model can be chosen to develop these skills. This research method uses a qualitative approach with research subjects of 25 students. Based on the results of research conducted through observation, documentation and interviews, it can be concluded that the application of the connected learning model has proven effective in improving students' communication skills. Students show significant development in their ability to convey ideas, argue logically, and use persuasive language. The connected learning model encourages collaboration between students through group assignments and discussions. This not only improves their speaking and listening skills, but also strengthens their ability to work in a team, share ideas, and give and receive feedback constructively so that their communication skills are well honed.